Reversed Crystal Growth - Zhou, Wuzong (Crystals (Basel), 2019)
In the last decade, a reversed growth route has been found in many crystal growth processes. In these systems, a single crystal does not develop from a single nucleus. The precursor molecules/ions or nanocrystallites aggregate into some large amorphous or polycrystalline particles. Multiple-nucleation on the surface of the amorphous particles or surface re-crystallization of the polycrystalline particles then takes place, forming a single crystal shell with a regular morphology. Finally, the crystallization extends from the surface to the core to form single crystals. This non-classical crystal growth route often results in some special morphologies, such as core-shell structures, hollow single crystals, sandwich structures, etc. This article gives a brief review of the research into reversed crystal growth and demonstrates that investigation of detailed mechanisms of crystal growth enables us to better understand the formation of many novel morphologies of the crystals. Some unsolved problems are also discussed.